PENERAPAN MODEL PEMBELAJARAN SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 105 PEKANBARU - Juli Lumbangaol; Lazim N Lazim N; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was carried out because of the low learning outcomes of social studies of grade IV in SD Negeri 105 Pekanbaru. The class consist of 35 students grade IV who reached the KKM (70) are 15 students (42,86%) and students who have not yet reached the KKM is 20 students (57,14%) with average rating of class 60,97%. The purpose of this research is to improve the learning achievement of social studies of grade IV in SD Negeri 105 Pekanbaru with the implementation of the snowball throwing model. The result of this research shows that the average value of basic score is 60,97 an increased in cycle 1 become 70,14. In cycle 2 the average value increased become 79,29. The activity of the teacher on the first meeting of the cycle 1 got was 65,63% with the enough category. The second meeting was 78,13 with the good category. On the first meeting of the cycle 2 teacher activity increased become 87,50% with the good category, at the second meeting become 93,75% with the very good category. The activity of the students on the first meeting of the cycle 1 got was 65,63% with the enough category, the second meeting was 78,13% with the good category. At the first meeting of the cycle 2 activity of students was 84,38% with the good category and the second meeting was 90,63% with the very good category. From this research it can be concluded that implementation of the snowball throwing learning model can be improve students learning outcomes of social studies of grade IV SD Negeri 105 pekanbaru.Keywords: snowball throwing, social studies outcomes